Grade Uncertainty and its Impact on Ore Grade Reconciliation between the Resource Model and the Mine - Parhizkar, A.; Ataei, M.; Moarefvand, P.; Rasouli, Vamegh (Polish Academy of Sciences, 2011)
Major differences between estimated grade and actual grade are a usual problem in many open pit mines. The estimated grade is predicted in exploration stage from data obtained from boreholes, whereas the actual grade would be determined only after the mining operation. The poor reconciliation between the values of estimated and actual grades can cause major economic losses to the mining industry. Many different factors affect the reconciliation process in a mining operation. The nature of the orebody, the random uncertainty and the systematic errors are three main sources affecting the reconciliation process in exploration stage of the orebody. In this paper each source of uncertainty is studied and a probabilistic model is presented to determine the role of each item in total uncertainty of the grade parameter. The model ability was investigated in the study of real data taken from an iron open pit mine in Iran. The results showed the systematic uncertainty, the nature of the orebody and the random uncertainty are the main causes of poor reconciliation in the case study respectively.